Provision of repeating the Azaan three times if the Imam settled on the Membar on Friday in Malikite school - Chandoul, Amara Saad (Journal of Islamic Sciences, 2019)
In the Arab Maghreb countries, the matter took place in Friday’s azaan, that if the imam settled on the Membar (pulpit) on Friday, they made al-Nida (called) for prayer three times. In recent years, there has been considerable controversy over the subject, as some public people have said that it only calls for a single call to the community, unlike what people used to do. Some enthusiastic young people have come to prevent the repetition of the prayers if the Imam is forced to sit down in the podium and to bequeath those who authorize it, and only if some of the muftis ruled that prayer should not be allowed in the mosque where it calls for three. The reason for studying the subject and investigating the truth was that, through this paper, we found that the azan’s call (al-Nida ) was three if the Imam was to be on the podium from the Sunnah, unlike what the people went to and understood, and that it was a matter of ignorance of the doctrine that people would change what was done without research and education. The researcher adopted the descriptive approach in the collection of texts. He used the analytical and deductive methodology in the whole knowledge. The research resulted that if the imam settled on the Membar on Friday, it is diferred to made al-Nida for prayer between being unique or repeating three times, and that both of the two opinions are really in itself. Infact, there are no provision for the validity of one and subtract the other.